Penggunaan Media Audio Visual Untuk Meningkatkan Prestasi Belajar Akidah Akhlak Siswa: Indonesia - sholahudin din; Nabila (Sekolah Tinggi Ilmu Tarbiyah Al- Kifayah Riau, 2021)
This study aims to improve student achievement through the use of audio-visual media. This research was applied to fifth-grade students of Madrasah Ibtidaiyah Negeri 4 Muaro Jambi in the first semester of the 2019/2020 school year. This research is classroom action research or Classroom Action Research with a cycle design. Data collection techniques using observation, tests, and documentation. Data were analyzed through descriptive qualitative data analysis was carried out on each data collected, both quantitative and qualitative data. The results showed that learning by using audio-visual media can improve students' learning achievement of moral aqidah. Student learning achievement increased from cycle I to cycle II. It can be concluded that the results of student learning activities in cycle I reached 62% and increased in cycle II to 88%. The results of student attitudes in the first cycle reached 72% but increased in the second cycle reaching 85.5%. This is evidenced by the student achievement scores at the end of the first cycle obtained an average of 69,54% with the category close to completion and student achievement scores increased in the second cycle obtained an average of 91.36% with the complete category.